Nasopharyngeal carcinoma patients from Norway show elevated Epstein-Barr virus IgA and IgG antibodies prior to diagnosis. (April 2022) - Simon, Julia; Brenner, Nicole; Reich, Sibylle; Langseth, Hilde; Hansen, Bo T.; Ursin, Giske; Ferreiro-Iglesias, Aida; Brennan, Paul; Kreimer, Aimée R.; Johansson, Mattias; Pring, Miranda; Nygard, Mari; et al.
Abstract: Background: IgA antibodies against few Epstein-Barr virus (EBV) proteins are established serological markers for nasopharyngeal carcinoma (NPC). We recently validated a novel, comprehensive EBV marker panel and showed that IgA, but also IgG antibodies against multiple EBV proteins are highly sensitive and specific for EBV-positive NPC at diagnosis. However, data about these novel biomarkers as prospective markers for NPC are sparse. Methods: This study included 30 incident NPC cases and 60 matched controls from the Norwegian Janus Serum Bank. For 21 NPCs, molecular EBV and human papillomavirus (HPV) status were assessed by EBER-ISH and HPV DNA/RNA testing by PCR, respectively. IgA and IgG serum antibodies against 17 EBV antigens were analyzed in prediagnostic sera of cases (median lead time 14 years) and controls using multiplex serology. Sensitivities were calculated using receiver operating characteristic analysis pre-specified to yield 90% specificity in the control group. From 10 cases, serial samples were available. Results: Quantitative EBV antibody levels were significantly elevated among all cases (p < 0.05) for three IgA and six IgG antibodies. The highest sensitivities for defining 12 EBER-ISH-positive NPCs were observed for BGLF2 IgA (67%) and BGLF2 IgG (83%). Increased IgA and IgG antibody levels between the first and last draw before diagnosis were observed for EBER-ISH positive, but not for EBER-ISH negative NPCs. Among 21 molecularly analyzed NPCs, 4 EBER-ISH negative NPCs showed concomitant positivity to HPV type-specific DNA and RNA; 3 NPCs were HPV16 and 1 NPC was HPV18 positive. Conclusion: Both, EBV IgA and IgG antibody levels are significantly elevated many years before diagnosis of EBV-positive NPCs in Norway, an NPC low-incidence region. This study provides insights into one of the largest available prospective sample collections of NPCs in a non-endemic country. Highlights: We studied Nasopharynx cancer in Norway, where it is a very rare disease. EBV and HPV positivity in nasopharynx cancer are mutually exclusive. EBV antibody kinetics years prior to diagnosis differ in EBV+ /- Nasopharynx cancer.